Dynamics of oil price shocks and stock market behavior in Pakistan: evidence from the 2007 financial crisis period - Khalil Jebran; Shihua Chen; Gohar Saeed; Alam Zeb (Financial Innovation, 2017)
Background: The aim of this study is to investigate the effect of the oil price and its volatility on the stock market of Pakistan before and after the 2007 financial crisis period. Methods: The analyses are carried out on daily data for the period from July 31, 2000 to July 31, 2014. This study uses several econometric techniques for the analyses, namely, the Johansen-Juselius cointegration test, generalized autoregressive conditional heteroskedasticity (GARCH) model, exponential generalized autoregressive conditional heteroskedasticity (EGARCH) model, variance decomposition method, and impulse response function. Results: The results of the cointegration method indicate a significant long-run association between stock market and oil prices in the pre-crisis period. The EGARCH model shows that oil price returns have a significant effect on stock market returns in both sub-periods, while the result for the GARCH model is significant only in the post-crisis period. We find a significant effect of oil price volatility on the stock market in both sub-periods from the GARCH model. Furthermore, the EGARCH model shows an asymmetric effect of oil price volatility on the stock market in the pre-crisis period. Variance decomposition shows that stock market variations are mostly explained by self-innovation. Moreover, the impulse response function results show that oil price shocks affected the stock market adversely in the pre-crisis period but positively in the post-crisis period. Conclusions: This study suggests that economic policymakers and investors should consider the oil price as an important factor affecting stock market returns.
Keywords: 650; Oil price shocks; EGARCH; GARCH; Financial crises; Pakistan